Marketing information products and services : a primer for librarians and information professionals - Jain, Abhinandan K.; International Development Research Centre Canada (New Delhi ; New York: Tata McGraw-Hill Pub. Co., 1999)
Contributed articles presented at a workshop held in 1994.
"International Development Research Centre."
Includes bibliographical references.
Keywords: Libraries -- -- Public relations -- -- India; Information services -- -- Marketing. -- -- India; Information services -- -- Public relations -- -- India; Marketing research